2007
DOI: 10.1002/jcp.21129
|View full text |Cite
|
Sign up to set email alerts
|

Complement 3 is involved in changing the phenotype of human glomerular mesangial cells

Abstract: Complement activation contributes to tissue injury in various forms of glomerulopathy and is characterized by deposition of complement components, which accelerates the progression of chronic renal damage. We recently reported that complement 3 (C3), a critical component of the complement system, is associated with the synthetic phenotype of vascular smooth muscle cells. It is possible that C3 stimulates mesangial cells to assume the synthetic phenotype to, in turn, induce glomerular injury and sclerosis. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 34 publications
0
23
1
Order By: Relevance
“…These differences may relate to the ability of the heavy chain to activate complement, a property that light chains lack. Complement activation, which is typically detectable by immunofluorescence in these cases, may have direct effects on mesangial cells and podocytes to promote matrix production and greater proteinuria (19,20). Patient outcome, however, was not statistically different between HCDD and LCDD.…”
Section: Discussionmentioning
confidence: 89%
“…These differences may relate to the ability of the heavy chain to activate complement, a property that light chains lack. Complement activation, which is typically detectable by immunofluorescence in these cases, may have direct effects on mesangial cells and podocytes to promote matrix production and greater proteinuria (19,20). Patient outcome, however, was not statistically different between HCDD and LCDD.…”
Section: Discussionmentioning
confidence: 89%
“…The capacity of C3a to induce a change in the phenotype of other renal cells has also been reported. Wan et al 45 demonstrated that C3a can change the phenotype of mesangial cells, which may have implications for understanding the effect of C3a in this mouse model of proteinuria.…”
Section: Discussionmentioning
confidence: 94%
“…Mesangial cells produce FH 86 and, in an inflammatory environment (IL-1 or TNFa), they produce C3. 87 Furthermore, the autoantigen in IgAN, polymeric Gd-IgA1, can itself stimulate mesangial cells to produce and secrete C3. 88 Activation products C3a and C5a can induce cultured human mesangial cells to produce DAF, a potent membrane-bound regulator of the alternative pathway.…”
Section: Where Complement Is Activated: From Soluble Circulating Immumentioning
confidence: 99%
“…This transition may explain the in vivo expansion of the mesangial matrix commonly observed in renal biopsies of patients with IgAN. 87 The effect has been shown to be dependent on C3a receptor, although another study using in situ hybridization failed to find C3a receptor expression on normal human mesangial cells. 91 …”
Section: Where Complement Is Activated: From Soluble Circulating Immumentioning
confidence: 99%